2019
DOI: 10.1093/pcp/pcz190
|View full text |Cite
|
Sign up to set email alerts
|

Genome-Wide Identification of Cassava Serine/Arginine-Rich Proteins: Insights into Alternative Splicing of Pre-mRNAs and Response to Abiotic Stress

Abstract: Serine/arginine-rich (SR) proteins have an essential role in the splicing of pre-messenger RNA (pre-mRNA) in eukaryote. Pre-mRNA with introns can be alternatively spliced to generate multiple transcripts, thereby increasing adaptation to the external stress conditions in planta. However, pre-mRNA of SR proteins can also be alternatively spliced in different plant tissues and in response to diverse stress treatments, indicating that SR proteins might be involved in regulating plant development and adaptation to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
20
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(24 citation statements)
references
References 65 publications
1
20
0
Order By: Relevance
“…Indeed, with the exception of Sl-RSZ21a, all other SR and SR-like genes are alternatively spliced (Figure 4). The absence of alternative splicing in at least one RSZ gene has been reported in A. thaliana, B. rapa, and Manihot esculenta (cassava) (Palusa et al, 2007;Yoon et al, 2018;Gu et al, 2020). Moreover, the conservation in alternative splicing between Arabidopsis and rice SR genes, for example in the introns flanking the RRM coding region (Kalyna et al, 2006), is confirmed here for tomato (Figure 4).…”
Section: Regulation Of Tomato Sr Protein-coding Genes In Different Tissuessupporting
confidence: 75%
See 1 more Smart Citation
“…Indeed, with the exception of Sl-RSZ21a, all other SR and SR-like genes are alternatively spliced (Figure 4). The absence of alternative splicing in at least one RSZ gene has been reported in A. thaliana, B. rapa, and Manihot esculenta (cassava) (Palusa et al, 2007;Yoon et al, 2018;Gu et al, 2020). Moreover, the conservation in alternative splicing between Arabidopsis and rice SR genes, for example in the introns flanking the RRM coding region (Kalyna et al, 2006), is confirmed here for tomato (Figure 4).…”
Section: Regulation Of Tomato Sr Protein-coding Genes In Different Tissuessupporting
confidence: 75%
“…The ortholog of NAC protein Solyc11g017470 in A. thaliana (AT1G01720) is induced after a treatment with abscisic acid (ABA) and is involved in abiotic stress responses (Jensen et al, 2013). An ABA-dependent regulation has been shown for several Arabidopsis and cassava SRs (Cruz et al, 2014;Gu et al, 2020) and therefore, considering that ABA is involved in HS response, we can assume an interplay of different regulatory networks to control SR transcription under high temperatures.…”
Section: Sr Genes Are Regulated At Multiple Levels In Response To High Temperaturesmentioning
confidence: 99%
“…Additionally, a few SR-like genes (e.g., SR45, SR45a) were found to have two RS domains instead of the one found in typical SR proteins [45,100,101]. Genome-wide identification of SR proteins in Brassica rapa [20], wheat, Brachypodium distachyon [44], tomato [36], and Cassava [43] resulted in 28, 40, 18, 19, and 18 SR genes, respectively. Of these, the expression of 22 and alternative splicing patterns of 17 genes in B. rapa were significantly altered in response to cold, heat, or oxidative stresses [20].…”
Section: Serine/arginine-rich (Sr) Domainmentioning
confidence: 99%
“…SR proteins are non-small nuclear ribonucleoproteins (non-snRNP) which form complex spliceosome machinery that mediates numerous events in pre-mRNA splicing [20,97]. The canonical SR domain proteins consist of one or two N-terminal RNA recognition motifs (RRMs), which bind to the RNA targets, and a serine-arginine or arginine-serine dipeptide-rich C-terminal-terminal region (RS domain) with a variable length [36,43,97]. Based on the domain organization structures and the presence of amino acid sequence motifs, SR proteins can be classified into six subfamilies: SR (two RRM), RS (two RRM, but the second RRM lacks SWQDLKD motif), SC (with just 1 RRM), SCL (SC-like with charged N terminal AA residues), RSZ (CCHC zinc knuckle), and RS2Z (two CCHC zinc knuckles) [44,98,99].…”
Section: Serine/arginine-rich (Sr) Domainmentioning
confidence: 99%
See 1 more Smart Citation